THE ROLE OF MUSLIM FAMILIES IN ANTICIPATION OF THE SPREAD OF LGBT IN SINGAPORE FROM THE PERSPECTIVE OF SADD AL-DHARĪʿAH - Razak Omar; Rizki Muhammad Haris (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2026)
This research is motivated by social and legal changes in Singapore following the revocation of Article 377A, which legalized same-sex relationships under state law, thus creating new challenges for Muslim families in upholding religious values. This study aims to analyze the role of Muslim families in anticipating the spread of LGBT ideology through the Sadd al-Dharīʿah approach as a preventive principle in Islamic law. The method used is a normative juridical approach combined with field studies to obtain empirical data from the community. The results show that families have a strategic role in shaping moral resilience through religious education, social supervision, and strengthening Islamic identity. The Sadd al-Dharīʿah approach has proven relevant as a preventive framework in preventing the normalization of behavior that is contrary to sharia. In conclusion, the integration of Islamic normative values ​​and an inclusive social approach can be a solution in maintaining harmony in Muslim families amidst dynamic social changes.